Quantification of 1-deoxynojirimycin content, ?-amylase inhibition activity, and secondary metabolites in four different mulberry accession leaves from Indonesia - YASINTA RATNA ESTI WULANDARI; WILLIAM FRANS; YANTI YANTI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wulandari YRE, Frans W, Yanti. 2025. Quantification of 1-deoxynojirimycin content, a-amylase inhibition activity, and secondary metabolites in four different mulberry accession leaves from Indonesia. Biodiversitas 26: 3047-3053. Mulberry (Morus spp.) is known to be one of the plants with potential as an antidiabetic. However, there is still limited information on the potential of mulberry leaves against diabetes, particularly mulberry from Indonesia. One of the compounds found in mulberry, namely 1-deoxynojirimycin (1-DNJ), has shown significant potential for diabetes. Therefore, this study aimed to analyze the content of 1-DNJ, the inhibitory activity of ?-amylase enzyme, and secondary metabolites found in 4 types of mulberry accessions from various regions in Indonesia. Mulberry plant samples were obtained from Bogor, Pati, as well as Situbondo, and their leaves were made into extracts. The samples were analyzed for 1-DNJ content using High Performance Liquid Chromatography (HPLC), a-amylase inhibitory activity through in-vitro tests, and secondary metabolite was determined with LCMS-QTOF. The results showed that accession 3 from Bogor had the highest 1-DNJ content with 0.357±0.003 mg 1-DNJ/g leaves. In terms of ????-amylase inhibitory activity, accession 3 also performed the best with an IC50 value of 5.1075±1.734 mg/mL compared to the acarbose with 2.062±0.424 mg/mL. Further analysis of extract found flavonoid groups such as luteolin, quercetin, and cyanidin 3,5-glucosidase, which could potentially contribute to the inhibition activity of ????-amylase. Compared to others, accession 3 from Bogor showed the most potential result due to its high 1-DNJ content and low IC50 value. Moreover, future studies were recommended to conduct in-vivo tests and examine the ability of mulberry leaves accession 3 in handling antidiabetic disease healing.